1999
DOI: 10.1128/jb.181.5.1444-1450.1999
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxylaminophenol Mutase from Ralstonia eutropha JMP134 Catalyzes a Bamberger Rearrangement

Abstract: 3-Hydroxylaminophenol mutase from Ralstonia eutrophaJMP134 is involved in the degradative pathway of 3-nitrophenol, in which it catalyzes the conversion of 3-hydroxylaminophenol to aminohydroquinone. To show that the reaction was really catalyzed by a single enzyme without the release of intermediates, the corresponding protein was purified to apparent homogeneity from an extract of cells grown on 3-nitrophenol as the nitrogen source and succinate as the carbon and energy source. 3-Hydroxylaminophenol mutase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Three nitrophenols support the growth of C. necator JMP134: 2,6-dinitrophenol (Ecker et al, 1992), 3-nitrophenol (Schenzle et al, 1997) and 2-chloro-5-nitrophenol (Schenzle et al, 1999a). The initial degradation pathway for 3-nitrophenol consists of the transformation into 3-hydroxylaminophenol and then into aminohydroquinone; these are catalyzed by a 3-nitrophenol nitroreductase (MnpA) and a 3-hydroxylaminophenol mutase (Fig.…”
Section: Catabolic Pathways For Nitrophenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three nitrophenols support the growth of C. necator JMP134: 2,6-dinitrophenol (Ecker et al, 1992), 3-nitrophenol (Schenzle et al, 1997) and 2-chloro-5-nitrophenol (Schenzle et al, 1999a). The initial degradation pathway for 3-nitrophenol consists of the transformation into 3-hydroxylaminophenol and then into aminohydroquinone; these are catalyzed by a 3-nitrophenol nitroreductase (MnpA) and a 3-hydroxylaminophenol mutase (Fig.…”
Section: Catabolic Pathways For Nitrophenolsmentioning
confidence: 99%
“…The 3-hydroxylaminophenol mutase was identified as a glutamine syntethase (Table 5) (Schenzle et al, 1999b). The initial degradation of 2-chloro-5-nitrophenol is analogous to that of 3-nitrophenol, and results in the formation of 2-amino-5-chlorohydroquinone (Schenzle et al, 1999a). The removal of the chlorine group in the latter intermediate is reductively mediated and produces aminohydroquinone, a common intermediate.…”
Section: Catabolic Pathways For Nitrophenolsmentioning
confidence: 99%
“…The presence of AA and HAA in the degradation pathway of 20 mM ONB led us to hypothesize that 2‐HABA is a substrate for two different enzymes, a reductase and a mutase. The reductase catalyzes the conversion of HABA to AA by reducing the hydroxylamino group to an amino group while the mutase converts HABA to HAA through a Bamberger‐like rearrangement [32]. Results of enzyme assays of both enzymes acting at the branching point support this hypothesis.…”
Section: Resultsmentioning
confidence: 82%
“…These authors found two genes encoding hydroxylaminobenzene mutase in nitrobenzene-degrading Pseudomonas pseudoalcaligenes JS45. Schenzle et al [39] described amino acid sequences of the NH 2 -terminus and of two internal sequences of a 3-hydroxylaminophenol mutase from Ralstonia eutropha JMP134. These sequences have no homologies to the deduced amino acid sequence of the two hydroxylaminobenzene mutases in P. pseudoalcaligenes JS45 [38].…”
Section: Mutase-catalyzed Formation Of Dead-end Metabolitesmentioning
confidence: 99%